A comprehensive evaluation of the impact of telemonitoring in patients with long-term conditions and social care needs: protocol for the whole systems demonstrator cluster randomised trial - Bower Peter; Cartwright Martin; Hirani Shashivadan P; Barlow James; Hendy Jane; Knapp Martin; Henderson Catherine; Rogers Anne; Sanders Caroline; Bardsley Martin; Steventon Adam; Fitzpatrick Raymond; et al. (BMC, 2011)
Abstract Background It is expected that increased demands on services will result from expanding numbers of older people with long-term conditions and social care needs. There is significant interest in the potential for technology to reduce utilisation of health services in these patient populations, including telecare (the remote, automatic and passive monitoring of changes in an individual's condition or lifestyle) and telehealth (the remote exchange of data between a patient and health care professional). The potential of telehealth and telecare technology to improve care and reduce costs is limited by a lack of rigorous evidence of actual impact. Methods/Design We are conducting a large scale, multi-site study of the implementation, impact and acceptability of these new technologies. A major part of the evaluation is a cluster-randomised controlled trial of telehealth and telecare versus usual care in patients with long-term conditions or social care needs. The trial involves a number of outcomes, including health care utilisation and quality of life. We describe the broad evaluation and the methods of the cluster randomised trial Discussion If telehealth and telecare technology proves effective, it will provide additional options for health services worldwide to deliver care for populations with high levels of need. Trial Registration Current Controlled Trials ISRCTN43002091